2022
DOI: 10.3390/w14010072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Aeration Strategy on NOB Suppression in Activated Sludge and Biofilm in a Hybrid Reactor with Nitrification/Denitrification

Abstract: The purpose of the study was to analyse the impact of aeration strategies defined by the changes in the duration of aerated sub-phases, the ratio between non-aerated and aerated sub-phase times (R), and dissolved oxygen concentrations (DO) on the suppression of nitrite-oxidizing bacteria (NOB) in activated sludge and biofilm developing in a hybrid reactor with nitrification/denitrification. The primary factor causing NOB suppression both in biofilm and in activated sludge was an increase in the R-value (from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…S.II.1.). This aligns with the observations made for the biofilm from hybrid systems [17,18]. Data presented in Figure 5 also suggest that irrespective of the research stage, nitriteoxidizing bacteria showed greater activity, which is consistent with qPCR results, where NOB were the predominant bacterial group in all samples.…”
Section: Nitrification Kinetics and Nitrifier Diversity In The Moving...supporting
confidence: 90%
See 4 more Smart Citations
“…S.II.1.). This aligns with the observations made for the biofilm from hybrid systems [17,18]. Data presented in Figure 5 also suggest that irrespective of the research stage, nitriteoxidizing bacteria showed greater activity, which is consistent with qPCR results, where NOB were the predominant bacterial group in all samples.…”
Section: Nitrification Kinetics and Nitrifier Diversity In The Moving...supporting
confidence: 90%
“…), the abundance of all studied bacteria increased by 6.9-fold, 8.1-fold, and 2.7-fold, for AOB, NOB, and Comammox bacteria, respectively. The same trend was observed in the biofilm from the aforementioned hybrid reactor, where, upon introducing intermittent aeration in the same regime, the abundance of these bacteria increased, despite the DO concentration being half as low as that in the mentioned study [17]. Each time, shortening the duration of subphases with aeration (increase in R) led to a drop in the activity of bacteria capable of oxidizing ammonia nitrogen by approximately 20% (from S.I.1.…”
Section: Nitrification Kinetics and Nitrifier Diversity In The Moving...supporting
confidence: 72%
See 3 more Smart Citations